Effect of Time and Reaction Speed on Making Liquid Soap in Terms of Viscosity and Density Values - Erna Astuti; Aster Rahayu; Endah Sulistiawati (Universitas Ahmad Dahlan, 2021)
Soap is a product from the hydrolysis of fats into fatty acids and glycerol under alkaline conditions, known as the saponification process. Many factors affect the saponification process to produce liquid soap with proper quality, including viscosity and density values. Saponification time and stirring speed are factors that affect the soap quality to be observed. Using strong bases and strong acids from electrolysis machines as well as coconut oil as a natural comperland are the innovations in this study. The results obtained are liquid soap in accordance with SNI 06-4085-1996, where the expected density ranges from (1.01-1.10 gr/cm3) and viscosity (400-20000 cP). Based on the current results, the most optimal results in accordance with SNI 06-4085-1996 are 24 hours for saponification time and stirring for 40 minutes, with a density of 1.083 gr/ml and viscosity of 482.0755 cP.